2018
DOI: 10.5483/bmbrep.2018.51.12.234
|View full text |Cite
|
Sign up to set email alerts
|

Functions of DEAD box RNA helicases DDX5 and DDX17 in chromatin organization and transcriptional regulation

Abstract: RNA helicases DDX5 and DDX17 are multitasking proteins that regulate gene expression in different biological contexts through diverse activities. Special attention has long been paid to their function as coregulators of transcription factors, providing insight about their functional association with a number of chromatin modifiers and remodelers. However, to date, the variety of described mechanisms has made it difficult to understand precisely how these proteins work at the molecular level, and the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 95 publications
(127 reference statements)
0
43
0
Order By: Relevance
“…Similarly, these SREs were enriched in genes responding to the pro-inflammatory cytokine IFN-α [GSE3920, 43], are within the A cluster genes (Figure 1) that steadily increase with BMI, TGF-β1 and IL-6 [GSE39820, 44]. DDX5, a Chromatin remodeler cofactor [73][74][75] (Figure 3, center) belonging to cluster B_II (Figure 1), is an enriched downstream target of both IFN-α and active CD4 + Th1 cells . It increases in response to cyclooxygenase 2 (COX2) [76] and is also associated with pro-inflammatory response [77].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, these SREs were enriched in genes responding to the pro-inflammatory cytokine IFN-α [GSE3920, 43], are within the A cluster genes (Figure 1) that steadily increase with BMI, TGF-β1 and IL-6 [GSE39820, 44]. DDX5, a Chromatin remodeler cofactor [73][74][75] (Figure 3, center) belonging to cluster B_II (Figure 1), is an enriched downstream target of both IFN-α and active CD4 + Th1 cells . It increases in response to cyclooxygenase 2 (COX2) [76] and is also associated with pro-inflammatory response [77].…”
Section: Discussionmentioning
confidence: 99%
“…DDX5 is an ATP-dependent RNA helicase belonged to the DEAD-box protein family [20]. Previous studies have suggested an important role for DDX5 in regulating transcription in conjunction with multiple, sequence-specific transcription factors [21].…”
Section: Discussionmentioning
confidence: 99%
“…First, they can directly bind to specific RNA substrates, use ATP hydrolysis energy to unwind RNA duplexes, facilitate RNA annealing, and/or organize RNA–protein complex assembly ( 30 , 31 , 32 , 33 ). Second, DDXs can partner with transcription factors to modulate gene transcription ( 24 , 30 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ). In human cancer cell lines, DDX5 interacts with β-catenin protein and the long non-coding RNA NEAT1 to promote oncogene expression ( 41 , 42 ).…”
Section: Introductionmentioning
confidence: 99%